Religio-cultural and poetic constructions of the Subaltern African woman (2012)
The colonial experience, particularly the introduction of Christianity and Islam in Africa, altered the African socio-cultural equation and ways of life. European and Arab missionaries diligently spread their religious beliefs which fused with some African cultural practices and subsequently determined the status of African women, in particular. Suffice it to say that colonialism, Christianity and Islam masculinised any territory upon which they inflicted themselves and dismantled the matriarchal system that mutually coexisted with patriarchy in some pre-colonial African societies. They also provided an ideological framework for the social roles of women, which subordinated them to their male counterparts. Besides, the poetic constructions of African women on the literary platform of Negritude largely contributed in reinforcing this subaltern image and secondary roles ascribed to African women, heightened by colonialism and promoted by new religious doctrines and practices. The textual representation of African women as mothers, in terms of their nurturing capabilities, placed them in an essentially problematic position, and conferred on them a purely domestic role. It is quite cheering to note, however, that this unhealthy subordination of the African woman is rapidly giving way to the notion of gender equity, founded on new religio-cultural principles, and facilitated by women’s access to western education, modernization, and the systematic ‘eboulement ’ or dismantling of the African patriarchal culture.